Restorative Justice for Users of Narcotics Through Implementation of Depenalization - Muhammad Ihsan; Maroni Maroni; Ruben Achmad (Fiat Justisia: Jurnal Ilmu Hukum, 2022)
Restorative Justice is a policy that puts a focus on recovery rather than retaliation. The Restorative Justice implementation, considered more effective in terms of Justice and effectiveness, makes the Restorative Justice policy renewal of the criminal law system in Indonesia. The writing of this article uses a descriptive-analytical research method that prioritizes a normative juridical approach, with the formulation of the problem regarding the role of Restorative Justice as an effort to reform criminal law and the implementation of Restorative Justice as an alternative step in law enforcement for narcotics crimes. The result of this article is that the policy regarding Restorative Justice in its application is an update in law, especially criminal law. Conventional Justice Policies which are considered ineffective in their application are now being updated through the Restorative Justice policy; in addition to the context of the application, which is not only applied within the scope of general criminal law, in Narcotics crimes, a criminal settlement mechanism is also applied using Restorative Justice policies as stated in the Circular Letter of the Supreme Court Number 4 of 2010 concerning Placement of Abuse, Victims of Abuse and Narcotics Addicts into Medical and Social Rehabilitation Institutions (SEMA.4/2010). Rehabilitation of a Narcotics defendant can be carried out if it meets the requirements described in the regulation.